Evaluation of Student Learning Motivation Based on Parenting Style: A Qualitative Study - Cut Ita Zahara; Azwarni (Community Medicine and Education Journal, 2023)
Learning motivation encourages the desire to learn so that students achieve success in school and in the future. The success achieved by students in learning cannot be separated from the role of parents in nurturing. This study was an evaluation of student learning motivation based on the parenting style conducted at SMPN 1 Matangkuli, North Aceh. This research is an observational study with a qualitative approach. The participants in this study were students of SMP Negeri 1 Matangkuli, North Aceh district, and their parents. A total of six students and their parents participated in this study. Data were collected through observation, interviews, and documentation. Interviews were conducted in a semi-structured manner with children and parents about the parenting style used in the family. The results showed that children with democratic parenting have a strong learning motivation. In this study, it was also found that all aspects of learning motivation were owned and experienced by the six participants. In conclusion, students' learning motivation is related to the parenting style they experience in their families. There are three parenting styles applied by parents, namely, authoritarian, democratic, and permissive parenting.